Stress testing with multiple scenarios: A tale on tails and reverse stress scenarios - David Aikman; Romain Angotti; Katarzyna Budnik (European Central Bank (ECB), 2024)
This paper proposes an operational approach to stress testing, allowing one to assess the banking sector's vulnerability in multiple plausible macro-financial scenarios. The approach helps identify macro-financial risk factors of particular relevance for the banking system and individual banks and searches for scenarios that could push them towards their worst outcomes. We demonstrate this concept using a macroprudential stress testing model for the euro area. By doing so, we show how multiple-scenario stress testing can complement single-scenario stress tests, aid in scenario design, and evaluate risks in the banking system. We also show how stress tests and scenarios can be optimized to accommodate different mandates and instruments of supervisory and macroprudential agencies.
Keywords: E37; E58; G21; G28; 330; macroprudential stress test; multiple scenarios; reverse stress testing; financial stability; banking sector risks; systemic risks